2021
DOI: 10.1002/tox.23345
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose cadmium exposure facilitates cell proliferation by promoter hypermethylation of RASSF1A and DAPK1 genes

Abstract: Cadmium (Cd) at low concentrations has a potential to promote cell proliferation. However, the molecular mechanisms of Cd‐induced proliferation are not well understood. Here, we reported that Cd (0–500 nM) significantly promoted the proliferation of HepG2 cells as demonstrated by elevated cell viability, more EdU‐positive cells and increased gene expression of KI‐67 and COX‐2. Meanwhile, the gene expression of DNA methyltransferases was found to be elevated while that of tumor suppressor genes DAPK1 and RASSF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…This finding is consistent with other studies that reported Cd-induced hypertrophy of cardiac muscle through thickening of the ventricles of the heart [31 & 32]. As stated by Wang et al [33], Zhang et al [34] and McCauley et al [32], this thickening may be due to increased cell proliferation associated with higher expression levels of the essential cell cycle genes. Furthermore, in rats exposed to Cd, heart hypertrophic remodeling is related to these alterations in embryonic gene expression [31].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with other studies that reported Cd-induced hypertrophy of cardiac muscle through thickening of the ventricles of the heart [31 & 32]. As stated by Wang et al [33], Zhang et al [34] and McCauley et al [32], this thickening may be due to increased cell proliferation associated with higher expression levels of the essential cell cycle genes. Furthermore, in rats exposed to Cd, heart hypertrophic remodeling is related to these alterations in embryonic gene expression [31].…”
Section: Discussionsupporting
confidence: 92%